2022
DOI: 10.1039/d2fo02192g
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in polysaccharides from Rose roxburghii Tratt fruits: isolation, structural characterization, and bioactivities

Abstract: Rosa roxburghii Tratt fruit (RRF), known in China as Cili, is a highly valued fruit that contains abundant functional and nutritional constituents, which has a variety of health-promoting benefits. Polysaccharides...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
(106 reference statements)
0
7
0
Order By: Relevance
“…26 RRP has the potential to stimulate the proliferation of immune cells, enhance the secretion of antitumor cytokines, and improve immune capacity to impede the progression of tumors. 26 RRP has high safety and good biocompatibility, and it has been utilized to stabilize antibacterial silver nanoparticles. 27 According to the literature, there have been no reports of the use of RRP in combination with photothermal agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 RRP has the potential to stimulate the proliferation of immune cells, enhance the secretion of antitumor cytokines, and improve immune capacity to impede the progression of tumors. 26 RRP has high safety and good biocompatibility, and it has been utilized to stabilize antibacterial silver nanoparticles. 27 According to the literature, there have been no reports of the use of RRP in combination with photothermal agents.…”
Section: Introductionmentioning
confidence: 99%
“…roxburghii fruit polysaccharide (RRP) mainly consists of galactose, galacturonic acid, arabinose, and glucose in varying molar ratios . RRP has the potential to stimulate the proliferation of immune cells, enhance the secretion of antitumor cytokines, and improve immune capacity to impede the progression of tumors . RRP has high safety and good biocompatibility, and it has been utilized to stabilize antibacterial silver nanoparticles .…”
Section: Introductionmentioning
confidence: 99%
“…Modern medical research has shown that RRT has a variety of biological effects, such as immune function regulation, sedation, delaying aging, and anti-tumor effects. Among them, its excellent antioxidant capacity has received much attention [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nutritionally, R. roxburghii Tratt contains high levels of vitamin C, superoxide dismutase (SOD), polysaccharides, and polyphenols, making it a potential source of edible and medicinal plants (Wang et al, 2021). R. roxburghii Tratt has possible hypoglycemic, antioxidant, and anti‐tumor activities and is gaining attention due to its great nutritional potential (Su et al, 2022).…”
Section: Introductionmentioning
confidence: 99%